(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This essay is a brief presentation of the cooperation of Jelena Dimitrijević (1862-1945), a recognized and influential Serbian writer, with the elite charitable organization The Circle of Serbian Sisters in the first half of the 20th century. The focus of the paper is the official periodical of this women’s association, the almanac Vardar, which was published in two stages (1906-1914 and 1921-1941). The essay offers a detailed list and analysis of the literary articles of Jelena Dimitrijević in Vardar, which, as it turns out, can be described as a feminophilic, only partially as a women’s magazine and not at all as a feminist one. The aim of the research, on the one hand, is a further consideration of the editorial policy of this almanac and the ideology of The Circle of Serbian Sisters on the whole. On the other hand, it also offers some new insights regarding the work of Jelena Dimitrijević.